2020
DOI: 10.1007/s10639-020-10288-z
|View full text |Cite
|
Sign up to set email alerts
|

Social media usage by higher education academics: A scoping review of the literature

Abstract: Despite extensive proliferation of social media in different domains, higher education academics' use of social media remains unclear. This paper addresses this gap in the literature by providing a scoping review, covering the last five years of extant literature. It compiles and analyses previous empirical studies concerning academics' usage of social media, the benefits of social media for academics, and the challenges and barriers that academics face when using or considering using social media. The review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 32 publications
1
61
0
1
Order By: Relevance
“…There are several indications that EFL teachers from both countries aim to introduce new pedagogical practices in the post-Covid situation. For instance, they reported that they might use social media to contact their students and use quiz-based tests, more online materials, blended learning courses, both online and offline activities and flipped approaches to teaching, contrasting Chugh et al ( 2021 )’s findings that teachers do not use social media for teaching due to a lack of awareness, skill and confidence.…”
Section: Resultsmentioning
confidence: 84%
“…There are several indications that EFL teachers from both countries aim to introduce new pedagogical practices in the post-Covid situation. For instance, they reported that they might use social media to contact their students and use quiz-based tests, more online materials, blended learning courses, both online and offline activities and flipped approaches to teaching, contrasting Chugh et al ( 2021 )’s findings that teachers do not use social media for teaching due to a lack of awareness, skill and confidence.…”
Section: Resultsmentioning
confidence: 84%
“…Also, some reviews have covered only particular SNSs, such as Twitter [8] and Facebook [9]. In addition, there are reviews which have only summarised relevant studies [7,19], or provided a general narrative on the use of social media in higher education [6,20]. This paper aims to supplement the existing reviews in this area and address their limitations.…”
Section: Related Workmentioning
confidence: 99%
“…Despite the many studies which have examined the effective use and limitations of social media for educational purposes, their findings have yet to be comprehensively reviewed and summarised. Relevant reviews have only provided an overview of the developments [6,7], or focused on a specific discipline [8] or SNS [9]. This paper aims to review the studies on the use of social media in higher education institutions, and identify the opportunities and challenges reported in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the education framework, the evidence supports the potential broader and promising use of social media in higher education. Social media has been recognized to provide clear benefits for career development, research, and teaching, including improved communication with various interested parties, increased opportunities and contacts, and increased student learning and satisfaction ( Chugh et al., 2021 ). Positive impacts of the use of social media have also been revealed regarding (a) learning processes (support, educational processes, improved communication and collaboration, academic performance) for both students and educators; (b) users' personality profile and learning style; (c) online learning platforms (learning management systems (LMSs); and (d) higher education in general ( Zachos et al., 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This perspective has high value, since teachers and higher education institutions currently have not yet fully exploited online social networks to support their activities ( Zachos et al., 2018 ). In this sense, the pedagogical possibilities of social media have still been only partially applied ( Manca, 2020 ), and many academics still do not use social media for teaching due mostly to lack of awareness, skill and confidence in using this emerging technology ( Chugh et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%